2012
DOI: 10.1177/1403494812458988
|View full text |Cite
|
Sign up to set email alerts
|

“No alcohol, no party”: An explorative study of young Danish moderate drinkers

Abstract: The study identifies a group of young people who have clearly defined restrictions as to what they consider positive drinking behaviour. As parents and long-term health consequences only have an limited influence on the respondents' drinking behaviour, these elements should not have primary focus in future interventions. In stead, interventions should take into account the social dynamics involved in drinking and recognise that the social qualities surrounding alcohol weighs higher among this group of young pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 7 publications
2
36
0
Order By: Relevance
“…The findings support Frederiksen et al’s [6] assertion that alcohol consumption is associated with pleasure and celebrations by demonstrating that female students are mainly social drinkers who derive pleasure in moderate drinking in parties. While women’s drinking is pleasurable, men view parties as opportunities to acquire social capital and present themselves as “drinking machos” by participating in drinking games.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The findings support Frederiksen et al’s [6] assertion that alcohol consumption is associated with pleasure and celebrations by demonstrating that female students are mainly social drinkers who derive pleasure in moderate drinking in parties. While women’s drinking is pleasurable, men view parties as opportunities to acquire social capital and present themselves as “drinking machos” by participating in drinking games.…”
Section: Discussionsupporting
confidence: 87%
“…Not only is alcohol use in such occasions considered to be ‘normal’ [6], female social drinkers suggest that drinking alcohol gives pleasure and make these occasions:When you go to parties, you don’t expect them to give you juice or soft drink. What you need is alcohol and when you take alcohol, it will make you feel the groove, it will make you be in the spirit of the party so you can dance…you just end up being happy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, heavier drinking youths (i.e., youths who reported higher continued volumes) were not likely to drink in party contexts. In support of these results, a small exploratory study with Danish youths reported that drinkers indicated they do not need to drink a great amount of alcohol at parties in order to fit in with others (Frederiksen et al, 2012). These findings suggest that risks associated with drinking at parties may inhere in drinking in these contexts by different drinkers and less in how much they drink in those contexts.…”
Section: Discussionmentioning
confidence: 86%
“…Evidence for these types of compound drug memories may be derived from numerous verbal reports of drug users that are able to consciously retrieve rather complex “What-Where-When” information of their drug-instrumentalization episodes (Waldorf et al, 1991; Heath, 2000; Boys et al, 2001; Boys and Marsden, 2003; Boyd et al, 2006; Frederiksen et al, 2012). One may argue that these are conscious self-analyses of one’s own instrumentally conditioned behavior.…”
Section: The Specific Nature Of Episodic Drug Memoriesmentioning
confidence: 99%